Approaches to fostering active learning techniques for generation Z in nursing education: concept review article - Jadhav, Huchcheshwar R.; Sethi, Deepika; Subrahmanyam, Nidigantla; Sharmila, Pauline; Tamang, Reshma; Surendran, Surya; Nelavala, Anjani Devi; R., Deepa N.; Umar, Mohammed (International Journal of Research in Medical Sciences, 2025)
Nursing education is undergoing a significant transformation as generation Z enters the field, requiring educators to adapt their pedagogical approaches to effectively engage and prepare these digital natives for the complexities of modern healthcare. Adapting medical curriculum to the needs of the generation Z may bridge the generational divides. Generation Z is the most diverse generation identified. With traits like tech-savviness, flexibility in learning, social relevance, creativity, self-expressiveness, predominant hands-on learners valuing practical skills, driven with immediate feedback, engaging learners, participatory, curious, collaborative, self-directed, preferring autonomy yet a short attention span, they demand comfortable, conducive learning environments that fulfil their learning goals. These tips expressed aimed to sensitize the instructors to merely act as facilitators with the help of the mentioned active strategies, thereby enhancing the satisfaction of both teachers and learners.